Management Accountants Role in Dependent and Independent Companies: Does Ownership Matter? - Yazdifar, Hassan; Askarany, Davood; Askary, Saeed (JABM JOURNAL of ACCOUNTING - BUSINESS & MANAGEMENT, 2008)
The issue of (changing) accountants roles has been given considerable coverage in recent years, in both professional and academic accounting literature. This paper contributes to the debate by comparing the roles of accountants in independent organisations with the roles of accountants in dependent, subsidiary organisations. Do accountants working in dependent organisations have larger or smaller roles, or different roles, to accountants working for independent organisations? One thousand qualified members of the Chartered Institute of Management Accountants (CIMA), UK, were randomly selected for a postal questionnaire survey. This survey provides evidence which contributes towards an understanding of the influence and role of parent companies in management accounting practices and the role of management accountants in their subsidiary companies. This study relies on the data collected through a questionnaire survey. However, the extent of the role and influence of parent companies, and also the ways in which they impact on subsidiary companies need to be studied in greater depth i.e., case study method. The findings of this study will assist business consultants, system designers and managers to understand the differences between dependent and independent companies when considering implementation of any changes in their existing management accounting systems and practices. Most of the evidence to date on the relationship between parent and subsidiary companies is subject to fairly basic analysis, and presented in very general terms. Thus, this paper aims to contribute to towards this important debate through making a comparison of changing roles between independent and dependent organisations.